IMPLEMENTASI KEBIJAKAN PROGRAM LISTRIK PINTAR DI KECAMATAN PALU TIMUR - Kadim, Rima (Katalogis, 2015)
This research aims at determining the implementation of smart electricity program policy in the Palu Timur District. The main theory used in this study is Edward III on four factors influencing policy implementation, they are communication, resources, disposition and bureaucratic. This is a qualitative research with a survey as an approach technique. Five informants were taken by using purposive sampling technique in this study. The result of this research shows that there are sub indicators that should be improved, they are physical facilities, policy implementer, and the attitudes of policy maker which end at good result of the creation.